Identification of Factors For Repeating Thorax Photos in Dr Modality at Pertamina Central Hospital (RSPP) - Mahmudah, Dian; Amaanullah, Gita Khairani; Dhea, Zamitra Mila; Hariri, Ahmad (Green Publisher Indonesia, 2026)
Although the Radiology Installation of Pertamina Central Hospital (RSPP) has used Digital Radiography (DR), repetition of thorax photos still occurs frequently due to various factors. This study aims to identify the factors causing repetition of thorax photos in the DR modality at Pertamina Central Hospital (RSPP), to minimize patients' radiation exposure risk. This study employed a descriptive mixed-methods approach. Data were collected through observation, documentation, and literature review. The sample consisted of data on thorax photo examinations over a 2-month period, from January 12 to March 12, 2025. The survey revealed 166 repeated thorax photos at the Radiology Installation of Pertamina Central Hospital (RSPP), with a repetition rate of 9.36% 4.6 times higher than the standard set by Decree of the Minister of Health Number 129/Menkes/SK/II/2008. Solutions are therefore needed to reduce thorax photo repetitions, based on the identified causative factors, to ensure patient safety